The Puberty Meaning of Autistic Adolescent in their Parents’ Viewpoint “Phenomenological Study” - Henny Indrawati; Ari Wahyudi (Department of Special Education, 2017)
Autistic teenagers have turbulence puberty period perceived to deviate from other teenagers such as the existence of sex manipulation, unstable emotions and interest in the opposite sex. The purpose of this study was to get describtion or meaning of the parents’ point of view about the adolescent autistic puberty, the parent’s anxiety in facing the adolescent puberty puberty, the parents’ expectations of adolescent puberty and the parents’ acceptance of adolescent puberty puberty. This study used a phenomenological qualitative approach by conducting with in-depth interviews. The research design consiststed of Pre-field work, followed by In the field consisting of gettng in, getting long, and getting out. Data working consisted of coding and categorizing to obtain conclusions. From analyzing data by using Flow Model, the research result of the puberty meaning for T’s parents was by interpretating T’s agression as God’s gift make the parents aware and learn more their son’s current condition as the final result is happiness. The puberty meaning for S’s parents was as a natural stage eventhough the puberty was different from the other average children. The conclusion of the research for T’s parents was interpreting the condition as God’s gift to their autistic teenagers and as something natural process that their adolescent must pass. While, for S’s parents was as a subject of self-introspection and learning the meaning of patience.Remaja autis mengalami masa pubertas turbulensi yang dirasakan menyimpang dari remaja lainnya seperti adanya manipulasi seks, emosi dan minat yang tidak stabil pada lawan jenis. Tujuan dari penelitian ini adalah untuk mendapatkan gambaran atau makna sudut pandang orang tua tentang pubertas autis remaja, kecemasan orang tua dalam menghadapi pubertas pubertas remaja, harapan orang tua terhadap pubertas remaja dan penerimaan orang tua terhadap pubertas pubertas remaja. Penelitian ini menggunakan pendekatan kualitatif fenomenologis dengan melakukan wawancara mendalam. Desain penelitian terdiri dari karya Pre-field work, diikuti oleh In the field yang terdiri dari gettng in, getting long, and getting out. Data kerja terdiri dari pengkodean dan pengkategorian untuk mendapatkan kesimpulan. Dari analisis data dengan menggunakan Flow Model, hasil penelitian tentang makna pubertas bagi orang tua T adalah dengan menafsirkan agresi T sebagai anugerah Tuhan membuat orang tua sadar dan belajar lebih banyak kondisi anak mereka saat ini karena hasilnya adalah kebahagiaan. Masa pubertas bagi orang tua S adalah sebagai tahap alami walaupun pubertasnya berbeda dengan anak-anak lain yang rata-rata. Kesimpulan dari penelitian untuk orang tua T adalah menafsirkan kondisi tersebut sebagai pemberian Tuhan kepada remaja autis mereka dan sebagai sesuatu proses alami yang harus dilalui oleh remaja mereka. Sedangkan untuk orang tua S adalah sebagai bahan introspeksi diri dan belajar arti kesabaran.